Bridging the Gap: A Comparative Analysis of Classic and Modern Literature - Yadav, Aditya Kumar (Journal of Advanced Research in English & Education; Vol 8 No 3 (2023): Journal of Advanced Research in English & Education, 2023)
This review article delves into the intricate relationship between classic and modern literature, exploring the nuanced similarities and disparities that define these two distinct epochs of literary expression. Through an in-depth examination of key thematic elements, writing styles, and societal influences, this analysis aims to unravel the threads connecting the timeless works of the past with the dynamic narratives of the present. By investigating the thematic continuity, evolution of writing styles, and the profound impact on contemporary discourse, this review provides a comprehensive exploration of the symbiotic interplay between classic and modern literature. Through this lens, we seek to offer readers a nuanced understanding of the rich tapestry that binds these literary traditions, examining how they shape and reflect the cultural, social, and philosophical landscapes of their respective eras and endure as a testament to the enduring power of storytelling across generations.